Social Work in Public Health and Hospitals 2016
DOI: 10.1201/b13133-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Stunting and Severe Stunting Among Under-Fives in North Maluku Province of Indonesia

Abstract: Background: Utilization of maternal health services is associated with improved maternal and neonatal health outcomes. Considering global and national interests in the Millennium Development Goal and Nigeria's high level of maternal mortality, understanding the factors affecting maternal health use is crucial. Studies on the use of maternal care services have largely overlooked community and other contextual factors. This study examined the determinants of maternal services utilization in Nigeria, with a focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
131
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(166 citation statements)
references
References 35 publications
30
131
5
Order By: Relevance
“…The analysis showed that mothers from wealthier households and women with higher educational achievement exclusively breast-feed their babies compared with mothers from poorer households and women with no schooling, respectively, perhaps reflecting that mothers from higher SES groups are more likely to access and respond to health messages at a health facility (36) compared with mothers from lower SES groups. A previous study found that primary education is the minimum level required to gain from health promotion messages and it empowers vulnerable populations -especially women -to act on health messages (37) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The analysis showed that mothers from wealthier households and women with higher educational achievement exclusively breast-feed their babies compared with mothers from poorer households and women with no schooling, respectively, perhaps reflecting that mothers from higher SES groups are more likely to access and respond to health messages at a health facility (36) compared with mothers from lower SES groups. A previous study found that primary education is the minimum level required to gain from health promotion messages and it empowers vulnerable populations -especially women -to act on health messages (37) .…”
Section: Discussionmentioning
confidence: 97%
“…Information received during health service contactsmore likely to be accessed by higher SES women (36,(53)(54)(55) may also be an important driver of trends in optimal feeding practices. A previous Nigerian study found that mothers who had more contact with health services received information on optimal feeding practices (33) .…”
Section: ·591 0·179mentioning
confidence: 99%
“…A study on maternal health care utilization in nine high-focus states in India noted that for women who belonged to scheduled castes or scheduled tribes, it was the intersection of their low SES status, their segregated habitation, and their lack of knowledge about maternal care that led to under-utilization of maternal health care services [40]. Studies about maternal health care utilization in Nigeria and Mali [3739] have stressed the importance of using a multilevel approach in understanding maternal health utilization [38]. These studies describe how higher levels of education interact with a host of pathways such as improved knowledge of health services and increasing autonomy at the individual level [39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies about maternal health care utilization in Nigeria and Mali [3739] have stressed the importance of using a multilevel approach in understanding maternal health utilization [38]. These studies describe how higher levels of education interact with a host of pathways such as improved knowledge of health services and increasing autonomy at the individual level [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Women who watch television or read newspaper/magazine more frequently had higher probability of initiating ANC visit in the 1st trimester and have at least 4 ANC visits, while those listening to radio frequently had higher probability of initiating ANC visit at 1st trimester compared to those who don't at all. A study in Nigeria has also shown that community media saturation was found to be a strong predictor of maternal health service utilization [31].…”
Section: Discussionmentioning
confidence: 99%